(untitled) (International Scientific Journal Alfraganus, 2024)
The article presents ways to optimize the teaching of technical methods in wrestling. The method of modeling the teaching of technical methods in the training of wrestling types was studied. A survey questionnaire was used among trainers about the effective use of modeling methods of training processes. In wrestling, it differs from other sports due to the fact that the athlete’s technical movements are many and varied. The classification, system and terms of wrestling techniques have been developed to regulate the technical actions of a wrestler and to create an opportunity for communication between specialists in this field.